2012
DOI: 10.1507/endocrj.ej12-0049
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of glucose metabolism even in Chinese PCOS women with normal glucose tolerance

Abstract: Polycystic ovary syndrome (Pcos) is the most common endocrine disturbance in women of reproductive age [1]. It is important to prevent glucose metabolic disorder of PCOS as early as possible since more than 40% of PCOS women might develop impaired glucose tolerance or type 2 diabetes [2,3]. However, the early interventions of improving glucose metabolism were seldom adopted because the glucose levels of PCOS women were normal before developing impaired glucose tolerance.Insulin resistance is a common feature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
2
17
0
3
Order By: Relevance
“…Overall, insulin resistance and the compensatory hyperinsulinemia affect 50-70% of women with PCOS (4,5). PCOS is associated with a higher prevalence of chronic low-grade inflammation, dyslipidemia, hypertension, obesity, impaired glucose tolerance, metabolic syndrome, diabetes and cardiovascular risk factors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, insulin resistance and the compensatory hyperinsulinemia affect 50-70% of women with PCOS (4,5). PCOS is associated with a higher prevalence of chronic low-grade inflammation, dyslipidemia, hypertension, obesity, impaired glucose tolerance, metabolic syndrome, diabetes and cardiovascular risk factors (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…PKOS 'dan etkilenen kadınlar kronik düşük dereceli inflamasyon, dislipidemi, hipertansiyon, obesite, bozulmuş glukoz toleransı metabolik sendrom diabet ve kardiyovasküler hastalıkların artmış riski ile birliktelik gös-terir 11,12 . Bu çalışmada olduğu gibi PKOS'lu kadınların açlık glukoz değerleri coğu zaman normal sınırlarda olmasına rağmen; glukoz intoleransına eğilimli oldukları bilinmektedir.…”
Section: Discussionunclassified
“…Bu metabolik yüke bir de vücut yağ kitlesi fazlalığı olarak bilinen obezitenin eklenmesi bu sendromdan etkilenen kadınların glukoz metabolizmasının daha da fazla bozulmasına yol açar. Hatta zayıf PKOS'lu kadınlardaki insülin duyarlılığındaki azalma seviyesinin PKOS'u olmayan obes kadınlarakine benzer derecede olduğu bildirilmiştir [11][12][13] . Androjen fazlalığı cemiyeti obez PKOS'luların zayıf PKOS'lulara kıyasla tip 2 diabetes mellitus gelişim riskinin daha fazla olmasından ötürü obes PKOS'lularda olası bozulmuş glukoz toleransı veya tip 2 diabetes mellitus varlığının incelenmesi amacı ile 2 saatlik glukoz yükleme testinin rutin olarak uygulanmasını önermektedir 14 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…IR is recognized as a major risk factor for the development of type 2 diabetes mellitus (T2DM), which is 5-to 10-fold higher in women with PCOS than in healthy controls [2]. A previous study showed that Chinese women with PCOS and normal glucose tolerance had higher IR than controls, even in lean subjects [3]. However, few studies have investigated IR in women with PCOS and normal glucose tolerance, especially in lean women with PCOS.…”
Section: Introductionmentioning
confidence: 99%